Arteriovenous malformation of the small intestine presenting with a transfusion-dependent anaemia in pregnancy. Issue 3 (8th March 2023) - Dunphy, Louise; Ford, Jonathan
Abstract : Gastrointestinal bleeding that originates in the small intestine is often difficult to diagnose. Bleeding from a small intestinal arteriovenous malformation (AVM) is rare, with congenital AVMs more commonly located in the rectum or sigmoid. There is a relative paucity of cases reported in the literature. In the gastrointestinal tract, it can cause acute and chronic bleeding, which can be fatal. Although the incidence of small bowel AVMs is quite low, such lesions can be identified as the bleeding source in patients with obscure gastrointestinal bleeding (OGIB) harbouring severe, transfusion-dependent anaemia. It can be exceedingly difficult to localise and diagnose gastrointestinal tract bleeding, particularly in cases of occult small bowel AVMs. CT angiography and capsule endoscopy can help to establish the diagnosis. Laparoscopy is an appropriate and beneficial treatment modality for small bowel resection. The authors present the case of a primigravida woman in her late 20s diagnosed with a symptomatic transfusion-dependent anaemia during her pregnancy. She developed OGIB and despite no history of chronic liver disease became encephalopathic. Due to her physical deterioration and uncertain diagnosis, her caesarean section was performed at 36+6 weeks to expedite investigations and treatment. She was diagnosed with a jejunal AVM and underwent coiled embolisation of her superior mesenteric artery. She became haemodynamically unstable and underwent a laparotomy and small bowel resection. A full non-invasive liver screen was negative, however, her MRI liver described multiple focal nodular hyperplasia (FNH) lesions raising the possibility of FNH syndrome in the context of a previous AVM malformation. A prompt stepwise, multimodality diagnostic approach is required to prevent patient morbidity and mortality.